(untitled) (Research, Society and Development, 2026)
Objective: To identify, through scientific evidence, the main consequences of congenital toxoplasmosis, as well as the main means of prevention for this pathology. Methodology: This study is an integrative literature review. The databases used were BVS (Virtual Health Library), Google Scholar, and SciELO (Scientific Electronic Library Online). Applying the selection criteria, reading the titles and abstracts resulted in 11 articles for the study. Results: A study with a population of pregnant women revealed that 40% of these women had negative serology for T. gondii, however, they present a risk for transplacental transmission. Another study reported that up to one-third of newborns with congenital toxoplasmosis may present with negative serology for Toxo-IgM at birth. In another study, the incidence of sensorineural hearing loss is clear, and a variation of up to 20% of conductive hearing loss. Conclusion: The challenges to improving the scenario of congenital toxoplasmosis in Brazil are diverse, ranging from training and capacity building, easy access to tests to ensure early diagnosis in Family Health Units, and guaranteeing treatment for pregnant women and newborns. Therefore, it is important to emphasize that health education measures for the prevention of toxoplasmosis should be reinforced through lectures, consultations, educational interventions, and guidance during prenatal care, especially within the Family Health Strategy.